The Developing Left Superior Cervical Ganglion of Pacas (Agouti Paca) - Melo, Samanta Rios; Nyengaard, Jens Randel; Oliveira, Felipe da Roza; Lobo Ladd, Fernando Vagner; Bigaram Abrahao, Luciana Maria; Machado, Marcia R. F. [UNESP]; Sasahara, Tais H. C.; De Melo, Mariana Pereira; Ribeiro, Antonio Augusto C. M. (Wiley-liss, 2009)
In this study the main question investigated was the number and size of both binucleate and mononucleate superior cervical ganglion (SCG) neurons and, whether post-natal development would affect these parameters. Twenty left SCGs from 20 male pacas were used. Four different ages were investigated, that is newborn (4 days), young (45 days), adult (2 years), and aged animals (7 years). By using design-based stereo-logical methods, that is the Cavalieri principle and a physical disector combined with serial sectioning, the total volume of ganglion and total number of mononucleate and binucleate neurons were estimated. Furthermore, the mean perikaryal (somal) volume of mononucleate and binucleate neurons was estimated using the vertical nucleator. The main findings of this study were a 154% increase in the SCG volume, a 95% increase in the total number of mononucleate SCG neurons and a 50% increase in the total volume of SCG neurons. In conclusion, apart from neuron number, different adaptive mechanisms may coexist in the autonomic nervous system to guarantee a functional homeostasis during ageing, which is not always associated with neuron losses. Anat Rec, 292:966-975, 2009. (C) 2009 Wiley-Liss, Inc.
Keywords: SCG; Stereology; physical disector; ageing; Pacas